METAL MELTS – NANOSTRUCTURED SYSTEMS - V. Yu. Stetsenko (Литьë и металлургия, 2014)
On the basis of thermodynamic analysis it is shown that metal melts are the nanostructured systems which consist of phases and atoms nanocrystals. Nanocrystalsmake 97% ofthemeltvolume.